Modeling the magnetic properties of lanthanide complexes: relationship of the REC parameters with Pauling electronegativity and coordination number1. Issue 28 (28th July 2015) - Baldoví, José J.; Gaita-Ariño, Alejandro; Coronado, Eugenio
<x xml:space="preserve">Abstract</x> The REC model has proven to be useful to study lanthanide SIMs. But do its effective charge parameters have any physical meaning? Here we relate Dr and Zi with the coordination numbers, valence and electronegativity.